ANALISIS ASUHAN KEPERAWATAN DENGAN TEKNIK ENDROPHIN MASSAGE UNTUK MENGATASI MASALAH KECEMASAN PADA IBU POST PARTUM PRIMIPARA - Refiana Gunawan (2022)
Primiparous post partum mothers who are unable to adapt to the changes that occur in themselves can experience anxiety. Post partum mother anxiety needs to be addressed as early as possible. Endorphin massage is one type of massage that can help the body stimulate endorphins in the body that can create a feeling of comfort so that it can reduce anxiety. The purpose of this study was to analyze nursing care by applying endorphin massage techniques to primiparous postpartum mothers who experience anxiety. Respondents involved in this study amounted to 2 primiparous mothers. The intervention patient was given an endorphin massage intervention and nursing care actions while in the treatment room, while the resume patient only received nursing care actions while in the treatment room. This intervention was carried out three times with a frequency of once per day for 30 minutes. Measurement of anxiety using the Postpartum Specific Anxiety Scale Research Short Form for Crises (PSAS-RSF-C) questionnaire. The results showed that there was a decrease in anxiety in the intervention patient from a score of 29 during the pre-test to a score of 22 during the post-test, while in the resume patient there was a decrease in anxiety from a score of 27 during the pre-test to a score of 24 during the post-test. Endorphin massage can reduce anxiety in primiparous postpartum mothers, so the authors recommend it as a complementary therapy to overcome anxiety.